Theoretical ‘Irfan and How It Differs from Philosophy - Ayatullah Jawadi Amuli (حکمت اسرا, 2011)
The aim of the paper is to shed light on subject matters in different branches of mysticism. Empirical, transmitted, rational demonstrational and intuitional knowledge are four sources of human knowledge through which various branches of sciences have been established. Among sciences, philosophy and theoretical mysticism (‘irfan) are derived from rational thinking more than others. According to the author, arguments in theoretical ‘mysticism do not merely rely on personal intuition and inspiration; rather its principles – like philosophy’s– are also supported by rational demonstration because it contains perceptional propositions. This is in contrast to practical mysticism which has no rational demonstration. It consists of practical advices for the wayfarer; however, according to the author, there are two further branches of practical mysticism– namely intuitional and transmitted mysticism. Intuitional mysticism is nothing more than the mystic’s personal intuitions which can be conveyed to others. Transmitted mysticism consists of pieces of practical advice narrated by mystics or the wayfarer– the advice and practical principle which they have already successfully experienced on the course of their own spiritual journeys.